In Situ Formation of Free Chlorine During ClO2 Treatment: Implications on the Formation of Disinfection Byproducts - Rougé, V.; Allard, Sebastien; Croue, Jean-Philippe; Von Gunten, U. (American Chemical Society, 2018)
Chlorine dioxide (ClO2) is commonly used as an alternative disinfectant to chlorine in drinking water treatment because it produces limited concentrations of halogenated organic disinfection byproducts. During drinking water treatment, the primary ClO2 byproducts are the chlorite (50-70%) and the chlorate ions (0-30%). However, a significant portion of the ClO2 remains unaccounted for. This study demonstrates that when ClO2 was reacting with phenol, one mole of free available chlorine (FAC) was produced per two moles of consumed ClO2. The in situ formed FAC completed the mass balance on Cl for inorganic ClO2 byproducts (FAC + ClO2- + ClO3-). When reacting with organic matter extracts at near neutral conditions (pH 6.5-8.1), ClO2 also yielded a significant amount of FAC (up to 25%). Up to 27% of this in situ formed FAC was incorporated in organic matter forming adsorbable organic chlorine, which accounted for up to 7% of the initial ClO2 dose. Only low concentrations of regulated trihalomethanes were produced because of an efficient mitigation of their precursors by ClO2 oxidation. Conversely, dichloroacetonitrile formation from ClO2-induced generation of FAC was higher than from addition of FAC in absence of ClO2. Overall, these findings provide important information on the formation of FAC and disinfection byproducts during drinking water treatment with ClO2.